2012
DOI: 10.1002/mrc.3836
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional solid‐state NMR studies of the structure and dynamics of pectic polysaccharides in uniformly 13C‐labeled Arabidopsis primary cell walls

Abstract: Plant cell wall (CW) polysaccharides are responsible for the mechanical strength and growth of plant cells; however, the high-resolution structure and dynamics of the CW polysaccharides are still poorly understood because of the insoluble nature of these molecules. Here, we use 2D and 3D magic-angle-spinning (MAS) solid-state NMR (SSNMR) to investigate the structural role of pectins in the plant CW. Intact and partially depectinated primary CWs of Arabidopsis thaliana were uniformly labeled with (13)C and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 45 publications
4
91
0
Order By: Relevance
“…indicating the relative rigidity of the polysaccharides and a range of different environments. As expected, the major peaks in the spectrum are from glucose in the two main cellulose environments (C 1 : often assigned to crystalline and/or internal glucan chains; and C 2 : often assigned to amorphous and/or surface glucan chains)8910111228. Surprisingly, two distinct xylan carbon 4 (Xn4) peaks are clearly visible in the spectrum (82.2 and 77.4 p.p.m.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…indicating the relative rigidity of the polysaccharides and a range of different environments. As expected, the major peaks in the spectrum are from glucose in the two main cellulose environments (C 1 : often assigned to crystalline and/or internal glucan chains; and C 2 : often assigned to amorphous and/or surface glucan chains)8910111228. Surprisingly, two distinct xylan carbon 4 (Xn4) peaks are clearly visible in the spectrum (82.2 and 77.4 p.p.m.…”
Section: Resultssupporting
confidence: 66%
“…Xyloglucan was thought to crosslink microfibrils in primary cell walls. Multidimensional MAS NMR analyses of primary cell walls, pioneered in recent years by Hong and colleagues, have shown that, in contrast, only a minor portion of xyloglucan interacts with cellulose891011121314. In secondary cell walls, xylan (Supplementary Fig.…”
mentioning
confidence: 99%
“…Based on ssNMR spin diffusion, ∼50% of the cellulose surface makes contact with pectin [67]. Partial extraction of pectin from Arabidopsis cell walls rigidified the remaining matrix polysaccharides [67] and greatly slowed magnetic spin transfer from water to cellulose [68]. The latter result was attributed to water stabilization by pectins (spin transfer is reduced by rapid motions of water).…”
Section: Mechanical Coupling Of Cellulose Microfibrils By Xyloglucan mentioning
confidence: 99%
“…In comparison, matrix polysaccharides are much more mobile. For example, while 13 C T 1 relaxation times of cellulose are 5–10 s at 14.1–18.8 Tesla, matrix polysaccharides exhibit much shorter 13 C T 1 relaxation times of ~1 s [6, 14, 15]. Interestingly, the pectin T 1 relaxation is heterogeneous with at least two components: a fast component of ~0.4 s and a slow component of ~5 s (Fig.…”
Section: Challenges: Structural and Dynamical Heterogeneity Of Plamentioning
confidence: 99%